Metformin: a novel promising option for fertility preservation during cyclophosphamide-based chemotherapy. (4th January 2021) - Huang, Chu-Chun; Chou, Chia-Hung; Yang, Yu-Shih; Ho, Hong-Nerng; Shun, Chia-Tung; Wen, Wen-Fen; Chen, Shee-Uan; Chen, Mei-Jou
Abstract: Cyclophosphamide (CP) could cause severe gonadotoxicity via imbalanced activation of primordial follicles through PI3K/AKT/mTOR activation. Whether metformin, a widely prescribed anti-diabetes agent with mTOR inhibitory effect, could preserve ovarian function against CP toxicity is unknown. Female C57BL/6 mice were randomized into seven groups (n = 11), including control, CP-alone, CP + metformin, CP + sirolimus or everolimus, metformin-alone and sirolimus-alone groups. The duration of pharmaceutical treatment was 4 weeks. CP treatment significantly impaired ovarian function and fertility in mice. CP + metformin treatment significantly attenuated the gonadotoxicity comparing to CP-alone treatment (primordial follicle count: 17.6 ± 4.2 versus 10.3 ± 2.7 follicles/high-power field; P = 0.027). CP + metformin treatment also tended to increase antral follicular count (5.4 ± 1.1 versus 2.5 ± 1.6 follicles/section), serum AMH levels (4.6 ± 1.2 versus 2.0 ± 0.8 ng/ml) and the litter size (4.2 ± 1.3 versus 1.5 ± 1.0 mice per pregnancy), compared with CP-alone group. Expression of phospho-mTOR and the number of TUNEL-positive granulosa cells increased after CP treatment and decreased in the CP + metformin groups, suggesting the mTOR inhibitory and anti-apoptotic effects of metformin. In in-vitro granulosa cell experiments, the anti-apoptotic effect of metformin was blocked after inhibiting p53 or p21 function, and the expression of p53 mRNA was blocked with AMPK inhibitor, suggesting that the anti-apoptotic effect was AMPK/p53/p21-mediated. In conclusion, concurrent metformin treatment during CP therapy could significantly preserve ovarian function and fertility and could be a promising novel fertility preserving agent during chemotherapy. The relatively acceptable cost and well-established long-term safety profiles of this old drug might prompt its further clinical application at a faster pace.